If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + c = 22 Solving 6 + c = 22 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + c = 22 + -6 Combine like terms: 6 + -6 = 0 0 + c = 22 + -6 c = 22 + -6 Combine like terms: 22 + -6 = 16 c = 16 Simplifying c = 16
| c^4-9c^2+20=0 | | 5x+2=6x+-4 | | 0=9x-y+5 | | 8x^2+5x+7=0 | | Y=4x^2+2x+1 | | v^2+7v+30=0 | | z-(-40)=33 | | x+20=1/3(234) | | Y=-0.2(40)+50 | | 4x-27+(x+39)=180 | | 4X^2+2x+1=y | | x-16=2/3x | | 7x-(3x+10)=-x+15 | | 5x^2+33x=-18 | | p=5-4p | | 7x-3-2x=24-4x | | 6-(-5-11)= | | N^2+10=6 | | 2(7x-9)=3(8x-1) | | 17x-(-4x-5)=70 | | 7b+4b+9-5= | | X^2-3x-1=x+3 | | -3y-10=-5 | | 2t-7=-4 | | 5g=4 | | Y=-30+100 | | 5t-3=-13 | | -3x+39+15x=3 | | 3x-7+x=2x-5 | | -4a+9=25 | | -3+39+15x=3 | | 8v=7 |